2014
DOI: 10.1371/journal.pone.0106749
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Activity Limitations with the Health Assessment Questionnaire Predicts the Need for Support Measures in Patients with Rheumatoid Arthritis: A Multicenter Observational Study

Abstract: ObjectiveThis study investigated whether the Health Assessment Questionnaire (HAQ) can be used as an instrument to assess the need for social support measures that address activity limitations and participation issues in patients with rheumatoid arthritis (RA).MethodsThis multicenter observational study included patients with RA and disease duration of at least one year, consulting their rheumatologist for routine evaluation of disease activity. In the single study visit data on demographics, disease history a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Multiple studies highlight the importance of the perception of illness severity as perception relates to key patient‐related outcomes, including compliance and willingness to engage in treatment and seek essential resources . Patient‐ or parent‐reported measures of illness severity are essential to the conduct of health services and outcomes research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies highlight the importance of the perception of illness severity as perception relates to key patient‐related outcomes, including compliance and willingness to engage in treatment and seek essential resources . Patient‐ or parent‐reported measures of illness severity are essential to the conduct of health services and outcomes research.…”
Section: Discussionmentioning
confidence: 99%
“…Patient‐reported outcomes are widely recognised as a critical component of health services and quality‐of‐care research . Illness perceptions have been linked to patient‐related outcomes in both physical and mental health and are specifically associated with levels of psychological distress, help‐seeking behaviours and patient engagement with services or social supports . Reliable and valid patient‐ and parent‐reported measures of illness severity are essential to a range of health services, outcomes and health behaviour research.…”
mentioning
confidence: 99%
“…The setup of this multicenter observational study was extensively described in a previous study [ 14 ]. Briefly, the study included patients of at least 18 years of age who fulfilled the American College of Rheumatology diagnostic criteria for RA [ 19 ] and had a disease duration of at least one year.…”
Section: Methodsmentioning
confidence: 99%
“…We previously observed that HAQ score is a good predictor of the need for support measures in adult patients with RA and a disease duration of at least one year assessed against the expert opinion of the treating rheumatologist as a reference [ 14 ]. In this context, the HAQ performed better than SF-36 scores or DAS28 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In progress of time, rheumatoid arthritis leads to a decline in well-being and quality of life, depending on the individual's functional capacity and decreased mobility, decreased productivity, and difficulties in daily life performance [6,51,56,57]. For this reason, it is very important to implement the evaluation with an interdisciplinary approach [58].…”
Section: Occupational Therapy Evaluationmentioning
confidence: 99%